Systematic review of the rotavirus infection burden in the WHO-EMRO region - Selim Badur; Serdar Öztürk; Priya Pereira; Mohammad AbdelGhany; Mansour Khalaf; Youness Lagoubi; Onur Ozudogru; Kashif Hanif; Debasish Saha (Taylor & Francis Group, 2019)
Rotavirus gastroenteritis imposes a heavy burden on low- and middle-income countries. The World Health Organization defines the Eastern Mediterranean region (WHO-EMRO) as a diverse area in terms of socioeconomic status and health indicators. Rotavirus vaccination has been introduced, at least partially, in 19 out of the 22 EM countries; however, vaccine coverage remains low, and data on rotavirus disease burden is scarce. Available data on rotavirus prevalence, seasonality, vaccination status, and genotype evolution was systematically compiled following a literature review that identified 165 relevant WHO-EMRO epidemiology studies published between 1990 and 2017. Although the infectious agents responsible for acute gastroenteritis vary over time, rotavirus remained the leading cause of acute gastroenteritis in children, as seen in 76.3% of reviewed publications. Younger children (<2 years old) were at higher risk and thus increased vaccination coverage and surveillance systems are required to reduce the rotavirus gastroenteritis burden in WHO-EMRO countries.